2006
DOI: 10.1016/j.ygeno.2006.02.011
|View full text |Cite
|
Sign up to set email alerts
|

A wide-range phylogenetic analysis of Zic proteins: Implications for correlations between protein structure conservation and body plan complexity

Abstract: We compared Zic homologues from a wide range of animals. Striking conservation was found in the zinc finger domains, in which an exon-intron boundary has been kept in all bilateralians but not cnidarians, suggesting that all of the bilateralian Zic genes are derived from a single gene in a bilateralian ancestor. There were additional conserved amino acid sequences, ZOC and ZF-NC. Combined analysis of the zinc finger, ZOC, and ZF-NC revealed the presence of two classes of Zic, based on the degree of protein str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 34 publications
7
89
0
Order By: Relevance
“…1D). These results are consistent with a recently proposed hypothesis that the single ancestral Zic gene in the vertebrate ancestor has gone through one tandem duplication, two genome duplications, and occasional disappearance (Aruga et al, 2006). According to the model, Zic4 and Zic5 are counterparts on different chromosomes that arose by genome quadruplication.…”
Section: Structure Of Xenopus Zic4supporting
confidence: 91%
See 1 more Smart Citation
“…1D). These results are consistent with a recently proposed hypothesis that the single ancestral Zic gene in the vertebrate ancestor has gone through one tandem duplication, two genome duplications, and occasional disappearance (Aruga et al, 2006). According to the model, Zic4 and Zic5 are counterparts on different chromosomes that arose by genome quadruplication.…”
Section: Structure Of Xenopus Zic4supporting
confidence: 91%
“…The gene clustering profile and exon-intron boundaries in the ZF domains are conserved between Xenopus and mouse ( Fig. 1C; Aruga et al, 2006; data not shown). The neighbor-joining molecular phylogenetic tree indicates that the mammalian-amphibian common ancestor already possessed the five Zic genes (Fig.…”
Section: Structure Of Xenopus Zic4mentioning
confidence: 96%
“…1 P and S). In contrast, the expression of the anterior-specific gene DjZicB (16) was not induced in the anterior blastema at regeneration day 1, but rather decreased to the same level as that in the posterior blastema at day 3 in Djptc(RNAi) (Fig. 1 Q and S).…”
Section: Resultsmentioning
confidence: 93%
“…The Emx sequence was deposited in the DDBJ database with accession number AB439506. Tubifex Zic (Ttu-Zic, AB231870) and Tubifex Msx (Ttu-Msx, AB302957) cDNAs were previously described (Aruga et al 2006;Takahashi et al 2008). …”
Section: Pcr Cloning and Rt-pcr Analysismentioning
confidence: 99%
“…Recent molecular phylogenetic analyses have revealed that Zic family genes are found in a wide range of eumetazoans (Aruga et al 2006. Expression and functional analyses indicate that Zic zinc finger proteins commonly play roles in cell differentiation and proliferation in the early embryonic stages in Deuterostomia, Ecdysozoa, and Cnidaria (reviewed in Aruga 2004;Merzdorf 2007).…”
Section: Introductionmentioning
confidence: 99%